The Effect of Cesarean Delivery on Child Survival and Early Breastfeeding Practices: Global Data from 103 Provinces in the Eastern Mediterranean Region (International Journal of Scientific Research and Management (IJSRM), 2020)
Background: Early initiation of breastfeeding (EIBF) plays an important role in the reduction of infant mortality. Although Cesarean section (CS) can save lives it delays EIBF and thereby increases risk of mortality. Aim: To examine the relationship between CS and EIBF with child mortality. Methods: Data was recruited from recent demographic health surveys for 129 provinces of seven Eastern Mediterranean countries. The data was analyzed for breastfeeding initiation (EBFI) rates in the first hour and the first day, feeding prelacteals, delivery by skilled birth attendant (SBA), and delivery by CS, also neonatal mortality (NMR), infant mortality rates (IMR) and under-five mortality rates (U5MR). Statistical analysis was done using Pearson correlation and descriptive statistics. The economic cost of unnecessary CS correlated to mortality rates and EBFI. Results: Overall CS was inversely associated with EBFI in the first hour after birth (r-0.2, P=0.1), intake of prelacteals (r-0.3, P=0.008) and NMR (r-0.3, P=0.1), IMR (r-0.4, P=0.0001), and U5MR (r-0.4, P=0.0001) at P<0.05 and positively associated with EBFI in first day (r0.2, P=0.06). CS below the recommended level by WHO (<15%) was inversely associated with IMR. Moderately high CS >18% was inversely correlated with EBFI and positively correlated with intake of prelacteals, NMR and IMR. Very high CS >40 was inversely correlated with mortality at P<0.01. Unnecessary CS was significantly inversely correlated with U5MR. Conclusions: CS when unnecessary or by unskilled birth attendant, is a threat to child survival. Breastfeeding initiation, as early as possible skin-to-skin, is recommended to alleviate the outcome of CS.